KASHFI TERMIZI AND TERMIZ LITERARY SCHOOL - Aliev Shakir Jorakulovich (American Journals Publishing, 2022)
The city of Termiz has long been known to the world as "Madinat Ar-Rijol". It is mentioned in scientific-historical sources that many mystic scholars flourished in this land. Razin Tirmizi, Ja'far ibn Ali Tirmizi, Abu Sahl Tirmizi, Yusuf Hayat Tirmizi, Hakim Tirmizi, Warraq Tirmizi, Sayyid Burhoniddin Muhaqqiq Tirmizi, Sufi Allahyar, Mawlawi Jununi and other scholars of Sufism can be cited as examples.
Keywords: Kashfi Termizi, scientific heritage, Termiz literary school.